The different types of ethnic affiliation in M.G. Vassanji`s "No New Land" - Abbas, Hussein Ali; Mani, Manimangai; Wan Yahya, Wan Roselezam; Singh, Hardev Kaur Jujar (Australian International Academic Centre, 2017)
Establishing a sense of affiliation to ethnicity is one of the most controversial issues for people who are displaced in countries that are far away from their motherland.The colonisation of the British over Asia and Africa in the nineteenth century resulted in the mass movement of Indian workers from India to Africa. These workers were brought in to build railways that connected the British colonies in East Africa namely Kenya, Tanzania, and Uganda. While the arrival of the Indian workers is considered as a kind of colonial practice, but their deportation in the post-independence years is seen as a part of decolonization. These Indians were forced to leave Africa as they were blamed for being non supportive of the Africans who were then engaged in armed struggles against the British colonialists. This study is based on the lives of these deported Indians as depicted in the novel titled No New Land by M.G. Vassanji. M.G.Vassanji is a Canadian novelist whose family was also deported from Dar Esslaam, Tanzania. He also describes how the Indian Shamses were strict in affiliating with the different social and cultural background they found in their new home, Canada. This research examines the theme of affiliation and the experiences of these migrants. This study will show that South Asians in Canada are strict in their affiliation to their ethnic values. Secondly, it will expose the three types of affiliation and finally show how the author deals with affiliation as a part of the community’s ethnic record that must be documented.